Doxorubicin‐induced cardiotoxicity is maturation dependent due to the shift from topoisomerase IIα to IIβ in human stem cell derived cardiomyocytes. Issue 7 (20th May 2019) - Cui, Ning; Wu, Fujian; Lu, Wen‐Jing; Bai, Rui; Ke, Bingbing; Liu, Taoyan; Li, Lei; Lan, Feng; Cui, Ming
Abstract: Doxorubicin (DOX) is widely used to treat various cancers affecting adults and children; however, its clinical application is limited by its cardiotoxicity. Previous studies have shown that children are more susceptible to the cardiotoxic effects of DOX than adults, which may be related to different maturity levels of cardiomyocyte, but the underlying mechanisms are not fully understood. Moreover, researchers investigating DOX‐induced cardiotoxicity caused by human‐induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) have shown that dexrazoxane, the recognized cardioprotective drug for treating DOX‐induced cardiotoxicity, does not alleviate the toxicity of DOX on hiPSC‐CMs cultured for 30 days. We have suggested that this may be ascribed to the immaturity of the 30 days hiPSC‐CMs. In this study, we investigated the mechanisms of DOX induced cardiotoxicity in cardiomyocytes of different maturity. We selected 30‐day‐old and 60‐day‐old hiPSC‐CMs (day 30 and day 60 groups), which we term 'immature' and 'relatively mature' hiPSC‐CMs, respectively. The day 30 CMs were found to be more susceptible to DOX than the day 60 CMs. DOX leads to more ROS (reactive oxygen species) production in the day 60 CMs than in the relatively immature group due to increased mitochondria number. Moreover, the day 60 CMs mainly expressed topoisomerase IIβ presented less severe DNA damage, whereas the day 30 CMs dominantly expressed topoisomerase IIα exhibited much more severe DNA damage. These results suggest that immature cardiomyocytes are more sensitive to DOX as a result of a higher concentration of topoisomerase IIα, which leads to more DNA damage.